THEORETICAL FOUNDATIONS OF DEONTOLOGICAL TRAINING FOR RELIGIOUS STUDIES STUDENTS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the theoretical foundations of deontological training for undergraduate and graduate students in General Religious Studies programs. Given the sensitive nature of religious knowledge, the multicultural and pluralistic environment of contemporary societies, and the academic responsibility of future religious scholars, deontological competence has become an essential pedagogical priority. The study analyzes philosophical, cultural, legal, and pedagogical bases of deontological education and proposes a comprehensive conceptual model suitable for modern higher education institutions. Using methods of conceptual analysis, comparative review, structural–functional analysis, and theoretical modelling, the research identifies the core components and competencies required to prepare ethically responsible religious scholars. The results demonstrate that traditional ethics courses are insufficient for addressing the unique dilemmas faced by Religious Studies students, and thus require an integrated curriculum including case-based learning, dilemma training, academic integrity instruction, and interfaith communication practice. The article provides a detailed framework for universities to incorporate deontological training consistently throughout the Religious Studies curriculum and concludes with recommendations for future professional development practices.